Monitoring of Food Fouling in A Plate Heat Exchanger Using Heat Flux Sensor - Navaphattra Nunak; Worapanya Suthanupaphwut; T. Suesut (My University, 2025)
This article aims to describe the effect of fluid flow rate on soymilk fouling in a flat plate heat exchanger at a surface temperature of 95 °C using a foil heat flux sensor. The experiment was conducted in the pilot-scale fouling test rig for 6 hours each run. Five product flow rates of 1.5, 3.0, 4.5, 6.0, and 7.5 1/min were studied. The results showed that a heat flux sensor could be used to real-time monitor the changes of soymilk fouling deposits formed on the heated surface. Fouling curves of soymilk at flow rates of 3.0 and 4.5 1/min exhibited a falling rate pattern, while at flow rate of 1.5 showed an asymptotic pattern. It was found that the thickness of fouling decreased with increasing product flow rate in the range of 1.5 - 4.5 1/min. At higher flow rates, only a slightly thin film of fouling layer was observed.
Keywords: Evolutionary Algorithms and Applications